La programación mixta como herramienta para la solución de problemas de Planeación Agregada Multietapas - Kalenatic, Dusko; López Bello, Cesar Amilcar; González Rodríguez, Leonardo José (Ingeniería, 2008)
This paper describes, the development and testing of a mathematical programming model of serial multiperiod ag gregate production planning, multistage, with various sources for process stage, including concave cost and backlogging decision of finished product, the problem may be solved with mixed integer programming approaches.